Problematika Kepatuhan Pejabat Tata Usaha Negara dalam Eksekusi Putusan Pengadilan Tata Usaha Negara - Amalia, Riska Ari; Ashari, Ashari; Kafrawi, Rachman Maulana; Setiawan, Agung (Faculty of Law Hang Tuah University, 2024)
The regulation of the execution of State Administrative Court (TUN) decisions in Law Number 51 of 2009 concerning the Second Amendment to Law Number 5 of 1986 on State Administrative Court does not include a mechanism for executing TUN decisions, which in practice has caused many problems that undermine legal certainty and justice for the public. The focus of the writing is to provide an understanding to the public about the urgency of implementing execution in administrative court decisions. The main issues include two aspects: the obstacles faced by administrative officials in executing administrative court decisions, and solutions to address the compliance problems of administrative officials in executing administrative court decisions. The research method used is a normative research method. The research findings indicate that the obstacles in the implementation of TUN Decisions are due to the non-compliance of TUN officials and the lack of enforcement power for TUN decisions. The solution to address the compliance issues of TUN officials in executing TUN Decisions is to file a maladministration complaint with the Indonesian Ombudsman to exert pressure and revise the PTUN law to provide enforcement measures against the relevant TUN officials.